THE INFLUENCE OF COMPETENCE, ENVIRONMENT AND WORK MOTIVATION ON THE PERFORMANCE OF EMPLOYEES PT PLN (PERSERO) UNIT INDUK PEMBANGUNAN SUMATERA BAGIAN UTARA - Ahmad Said Baashen; Abdul Rahim Matondang; Yeni Absah (CV. Radja Publika, 2023)
Professional and qualified employees will form high performance, both individually and in groups so that it has an impact on the effectiveness of the organization as a whole. The problem is how to create employees who can produce optimal performance so that organizational goals can be achieved. This study aims to determine the effect of employee competence, environment, and work motivation on employee performance at PT PLN (Persero) North Sumatra Main Development Unit. To determine the effect of employee competence, environment, and work motivation on the performance of employees of PT PLN (Persero) North Sumatra Development Main Unit, the population of this study was all employees of PT PLN (Persero) North Sumatra Main Development Unit, totaling 241 people while the sample was 150 people. Given the characteristics of employees who tend to be uniform, the sampling is done by random sampling method. The test results show that there is a positive and significant effect of competence, environment, and work motivation on employee performance. There is a positive and significant influence on employee performance, it means that competence, environment, and work motivation have an influence on employee performance both simultaneously and partially.